PENGARUH KONSENTRASI GULA TERHADAP MUTU SELAI KULIT JERUK BALI (Citrus maxima) - Gaffar, Rahmah; Lahming, Lahming; Rais, Muhammad (Jurnal Pendidikan Teknologi Pertanian, 2017)
This research aimed to determine the effect sugar concentration of the quality albedo pummelo jam. This research used method completely randomized design with 3 treatments and 3 repetitions. The parameters observed were water content, sugar content, pectin content, total undissolved solids, and organoleptic include taste, colour,smear,and aroma.The data were analyzed with analysis of variance Anova and continued by Duncan test. The results showed that the best treatment was albedo pummelo jam with sugar concentration 80%.